2019
DOI: 10.1007/s40279-018-01034-0
|View full text |Cite
|
Sign up to set email alerts
|

Exit Gluten-Free and Enter Low FODMAPs: A Novel Dietary Strategy to Reduce Gastrointestinal Symptoms in Athletes

Abstract: Exercise-associated physiological disturbances alter gastrointestinal function and integrity. These alterations may increase susceptibility to dietary triggers, namely gluten and a family of short-chain carbohydrates known as FODMAPs (fermentable oligo-, di-, monosaccharides and polyols). A recent surge in the popularity of gluten-free diets (GFDs) among athletes without celiac disease has been exacerbated by unsubstantiated commercial health claims and high-profile athletes citing this diet to be the secret t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
41
0
18

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 89 publications
2
41
0
18
Order By: Relevance
“…Gut discomfort has also been reported as a significant issue for endurance athletes such as triathletes [5] and ultra-endurance athletes [4]. Recent literature has reported improved gastrointestinal comfort with lower FODMAP (fermentable oligo-, di-, mono-saccharides and polyols) intake in athletes [27][28][29][30], and this may be an emerging consideration by some individuals. There were mixed responses about concerns for positive doping influencing food choice.…”
Section: Discussionmentioning
confidence: 99%
“…Gut discomfort has also been reported as a significant issue for endurance athletes such as triathletes [5] and ultra-endurance athletes [4]. Recent literature has reported improved gastrointestinal comfort with lower FODMAP (fermentable oligo-, di-, mono-saccharides and polyols) intake in athletes [27][28][29][30], and this may be an emerging consideration by some individuals. There were mixed responses about concerns for positive doping influencing food choice.…”
Section: Discussionmentioning
confidence: 99%
“…2 Tüm sporcularda görülme oranı %30-50 iken ultradayanıklılık sporcularında bu oran %90'lara kadar çıkabilmektedir. [1][2][3] Üst ve alt GİS'in orta ve yüksek şiddet seviyesindeki gastrointestinal semptomlarının, özellikle yoğun dayanıklılık egzersizleri sırasında sportif performansı olumsuz etkileyebileceği belirtilmektedir. 1,3 Egzersize bağlı gelişen gastrointestinal semptomlar, gün geçtikçe görülme sıklığı artan, bireylerin yaşam kalitesini olumsuz yönde etkileyen ve en sık rastlanan fonksiyonel gastrointestinal bir hastalık olan irritabl bağırsak sendromu (İBS)ndaki klinik belirtilere benzerdir.…”
unclassified
“…[1][2][3] Üst ve alt GİS'in orta ve yüksek şiddet seviyesindeki gastrointestinal semptomlarının, özellikle yoğun dayanıklılık egzersizleri sırasında sportif performansı olumsuz etkileyebileceği belirtilmektedir. 1,3 Egzersize bağlı gelişen gastrointestinal semptomlar, gün geçtikçe görülme sıklığı artan, bireylerin yaşam kalitesini olumsuz yönde etkileyen ve en sık rastlanan fonksiyonel gastrointestinal bir hastalık olan irritabl bağırsak sendromu (İBS)ndaki klinik belirtilere benzerdir. [3][4][5] Bu semptomlar; üst karın şişkinliği, geğirme, bulantı, kusma, epigastrik (mide bölgesindeki) ağrı, mide ekşimesi, karın ağrısı, dışkılama dürtüsü, ishal ve/veya gevşek sulu dışkı ve dışkıda kan görülmesi gibi belirtilerdir.…”
unclassified
See 1 more Smart Citation
“…The second paper [2] in the supplement examines the very timely topic of foods that contain gluten or fermentable oligo-, di-, monosaccharides and polyols (FODMAPS) and their roles in producing gastrointestinal (GI) symptoms in athletes. The author suggests that the popularity of gluten-free diets (GFD) among athletes may not be warranted as research investigating the effects of a GFD in nonceliac athletes has not shown positive effects when compared to a gluten-containing diet on GI health, systemic inflammation, perceptual wellbeing or performance.…”
mentioning
confidence: 99%